2014
DOI: 10.2138/am-2015-5055
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and natural ammonium-bearing tourmaline

Abstract: Due to the similar ionic radius of K + and NH 4 + , K-silicates can incorporate a significant amount of NH 4 . As tourmaline is able to accommodate K in its crystal structure at high and ultrahigh pressure, we test if this also holds true for NH 4 .Piston-cylinder experiments in the system (NH 4 ) 2 O-MgO-SiO 2 -Al 2 O 3 -B 2 O 3 -H 2 O at 4.0 GPa, 700 °C, with B 2 O 3 and NH 4 OH in excess produce an assemblage of tourmaline, phengite, and coesite. The tourmaline crystals are up to 10 × 40 μm in size. EMP ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 45 publications
1
4
0
1
Order By: Relevance
“…All three tourmalines show a small, but significant amount of Si at the octahedral Z site, which has already been observed for other synthetic tourmaline from high-pressure syntheses (Schreyer et al 2000;Wunder et al 2015).…”
Section: Emp and Sims Analysessupporting
confidence: 77%
“…All three tourmalines show a small, but significant amount of Si at the octahedral Z site, which has already been observed for other synthetic tourmaline from high-pressure syntheses (Schreyer et al 2000;Wunder et al 2015).…”
Section: Emp and Sims Analysessupporting
confidence: 77%
“…9 mV signal intensity that would be visible on a mass scan. Additionally, mica also incorporates significant amount of NH 4 , in the same order of magnitude as that recorded in tourmaline (e.g., Boyd, 1997;Wunder et al, 2015), and its δ 7 Li is similar whether it is analyzed by MC-ICP-MS or LA-MC-ICPMS. Second, tourmaline is pyroelectric (e.g., Hawkins et al, 1995), and it may have an impact on Li ion behavior in the sample or the laser cell.…”
Section: Accepted Manuscriptmentioning
confidence: 75%
“…First, there may be a 14 N ++ spectral interference at mass 7. A recent paper demonstrated that tourmaline could incorporate significant amount of NH 4 (up to 500 µg/g in natural samples) in its crystal lattice (Wunder et al, 2015). However, such interference would create a ca.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, for ammonium in a crystal, ν 1 and ν 2 bands may appear in IR spectra due to decreased symmetry. FTIR spectroscopy is very sensitive to N-H vibrations and has been used to analyze NH 4 + in minerals in previous studies (e.g., Busigny et al 2003b;Watenphul et al, 2009Watenphul et al, , 2010Zhang et al 2010;Wunder et al 2015;Vennari et al 2016). The polarized and unpolarized IR spectra of NH 4 + in phengite at room temperature are shown in Figure 2.…”
Section: Ftir Spectra Of Nh 4 + In Phengite At Room Temperaturementioning
confidence: 99%